JASLARDÍ SHAŃARAQLÍQ TURMÍSQA TAYARLAWDA SHAŃARAQTAǴÍ ETNOPSIXOLOGIYALÍQ FUNKCIYANÍŃ ORNÍ - Suletbaeva, E.S. (SCIENCE and SOCIETY, 2024)
The article analyzes socio-psychological and ethnopsychological features of the family and the importance of ethnopsychological function in preparing young people for family life. The family is the only permanent institution of preservation, improvement and transmission from generation to generation of its ethnic, including ethnopsychological features.